Students’ Perceptions Towards Technology-supported Collaborative Peer Feedback - Sa?lamel, Hasan; Çetinkaya, ?akire Erbay (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2022)
The enhancement of English writing skills is essential for academic success, and as one form of alternative assessment, peer feedback implementations are utilized to enrich writing instruction process. The advent of Web 2.0 tools has helped writing practitioners utilize various Cloud-based technologies including Google Docs to encourage learners collaborate and exchange comments on their written products. Responding to the frequent calls to conduct further investigations utilizing diverse e-platforms to find out the most effective ones, thereby helping informed practitioner decisions, the current study examined the opinions of preparatory students enrolled in an English Language and Literature Department towards peer collaboration through Google Docs. Overall, computer-supported collaborative writing process created a sense of community and was found welcoming both for feedback provider and receivers who had diverse gains. Yet, the implementation is not without its limitations with personal and technical dimensions. The findings suggest that for a rewarding online peer editing experience, practitioners need to justify their attempts to extend writing instruction and assessment outside school borders, negotiate the e-platform with learners, and train them about how to comment on written products objectively